Aging behavior of three-proof polyurethane coatings under UV radiation - Wang, Jianfa; Gu, Zheng; Zhao, Jie; Zhang, Susu; Li, Peiyao; Meng, Chao; Sui, Jinyong; Zhang, Xiaoyi; Hu, Shaokai; Pan, Jiaying; Li, Junyi (Polimery, 2022)
The influence of UV radiation on the physical and mechanical properties of polyurethane resins and three-proof polyurethane coatings was examined. Changes of mechanical properties and the gloss of resins and coatings were determined. The structure of materials was confirmed using scanning microscopy SEM and Fourier transform infrared spectroscopy FTIR; thermogravimetric TGA and DTG studies were also performed. It turned out that the gloss of finished protective coatings was worse than the gloss of individual resins, and aging significantly lowered these values (from 81.3° to 8.9° in case of resins and from 61.1° to 2.8° in case of coatings after 1200 hours of irradiation). Tensile strength of resins decreased constantly during aging while their elongation at break decreased than increased reaching minimum at exposure time of 100 hours. In case of coatings, both tensile strength and elongation at break firstly decreased than increased reaching minimum at exposure time of 800 hours; after long exposure time, more than 1200 hours, these properties decreased again.